The mystery of the orphan train - Warner, Gertrude Chandler, 1890-; Papp, Robert (Morton Grove, IL : A. Whitman, 2005)
The Aldens try to solve a series of mysteries which took place in a old hotel in Kansas which they visit.
3.
007-012.
Keywords: Boxcar children (Fictitious characters) -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Hotels -- Kansas -- Juvenile fiction; Orphans -- Juvenile fiction; Boxcar children (Fictitious characters) -- Fiction; Brothers and sisters -- Fiction; Hotels, motels, etc. -- Fiction; Orphans -- Fiction; Mystery and detective stories; Kansas -- Juvenile fiction; Kansas -- Fiction; Mystery fiction